Pengaruh Ekstrak Batang Bandotan (Ageratum conyzoides L.) Terhadap Pertumbuhan Fusarium oxysporum yang Menginfeksi Tanaman Cabai Merah Besar (Capsicum annuum L.) - Fadhilla, Nurul; Agustrina, Rochmah; Chrisnawati, Lili; Mahfut, Mahfut (Konservasi Hayati, 2023)
Fusarium oxysporum is a fungal pathogen that causes plant wilt which infects many horticultural crops, including red chili (Capsicum annum L.). The continual control of pathogenic fungus with synthetic pesticides can have a negative impact on the environment, so it is necessary to look for safe and environmentally friendly alternative pathogen control methods, one of which is by using natural pesticides. Bandotan (Ageratum conyzoides L.) is known as a weed, containing secondary metabolites with antifungal activity. This study aims to determine the effect of bandotan stem extract on the growth of Fusarium oxysporum in infected chili plants during the germination phase. The study was conducted using a Completely Randomized Design (CRD) with one treatment factor, namely the method of giving bandotan extract consisting of 5 replications. ANOVA results at α = 5% showed that 65% dry bandotan stem extract did not reduce Fusarium oxysporum growth on the red chili plants.